Sandwiched Cathodes Assembled from CoS2‐Modified Carbon Clothes for High‐Performance Lithium‐Sulfur Batteries. Issue 16 (2nd June 2021) - Xu, Jun; Yang, Likun; Cao, Shoufu; Wang, Jingwen; Ma, Yuanming; Zhang, Junjun; Lu, Xiaoqing
Abstract: Structural design of advanced cathodes is a promising strategy to suppress the shuttle effect for lithium‐sulfur batteries (LSBs). In this work, the carbon cloth covered with CoS2 nanoparticles (CC‐CoS2 ) is prepared to function as both three‐dimensional (3D) current collector and physicochemical barrier to retard migration of soluble lithium polysulfides. On the one hand, the CC‐CoS2 film works as a robust 3D current collector and host with high conductivity, high sulfur loading, and high capability of capturing polysulfides. On the other hand, the 3D porous CC‐CoS2 film serves as a multifunctional interlayer that exhibits efficient physical blocking, strong chemisorption, and fast catalytic redox reaction kinetics toward soluble polysulfides. Consequently, the Al@S/AB@CC‐CoS2 cell with a sulfur loading of 1.2 mg cm −2 exhibits a high rate capability (≈823 mAh g −1 at 4 C) and delivers excellent capacity retention (a decay of ≈0.021% per cycle for 1000 cycles at 4 C). Moreover, the sandwiched cathode of CC‐CoS2 @S/AB@CC‐CoS2 is designed for high sulfur loading LSBs. The CC‐CoS2 @S/AB@CC‐CoS2 cells with sulfur loadings of 4.2 and 6.1 mg cm −2 deliver high reversible capacities of 1106 and 885 mAh g −1, respectively, after 100 cycles at 0.2 C. The outstanding electrochemical performance is attributed to the sandwiched structure with active catalytic component. Abstract : Sandwiched cathodes constructed from CoS2 ‐modified carbon clothes (CC‐CoS2 ) are designed for high sulfur loading lithium‐sulfur batteries. The sandwiched cathode not only offers three‐dimensional (3D) current collector and host with enough voids for volume expansion to maintain the structural stability, but also promotes the physical encapsulation, chemical entrapment and catalytic conversion of polysulfides species to suppress the shuttle effect.